Political Power and Material Identity: Saudi Women in Real and Virtual Societies - Reem Ali Al Derham (15445463) (2023)
Real “material” societies differ from one society to another; and therefore, the impact of the globalized virtual society on them varies according to whether they are conservative, and subject to political authority, or open and liberal. This chapter attempts to link the economic factor in Saudi society and its positive impact on the economic and social rights granted to Saudi women in the Saudi Vision 2030, as well as on the Saudi leadership’s decisions related to Saudi women. The analysis focuses on the reduction of restrictions on their material identity, the “Black Abaya”. It then examines how these decisions were reflected in changing the colour and shape of the Saudi Abaya in material society first, before changing appearances in virtual society, and not the other way around. Other Information Published in: Social Change and Transformation in the Gulf Region License: https://creativecommons.org/licenses/by/4.0 See chapter on publisher's website: https://dx.doi.org/10.1007/978-981-19-7796-1_36